Does Organizational Commitment Mediate the Effect of JOB Satisfaction on OCB of Palm Company Employees? - Noor Khatimah; Meiske Claudia; Maya Sari Dewi; Akhid Yulianto (Center for Journal Management and Publication, 2023)
The purpose of this study was to determine the effect of job satisfaction on organizational citizenship behavior (OCB) through employees’ organizational commitment at the PT. Sajang Heulang-KKPA3 Estate. This study used a quantitative approach. The respondents of this study were 73 employees. The sampling technique used was proportionate stratified random sampling. The data collection technique used a questionnaire spread to 73 employees. The data collected was processed using structural equation modelling (SEM) analysis techniques with the application of SmartPLS Version 3.0. The results showed that there was a significant direct effect of job satisfaction on OCB; there was a significant direct effect of job satisfaction on organizational commitment; there was a significant direct effect of organizational commitment on OCB and Organizational Commitment partially mediated the effect of job satisfaction on OCB.